Controlled Hydrothermal/Solvothermal Synthesis of High‐Performance LiFePO4 for Li‐Ion Batteries. Issue 6 (7th May 2021) - Li, Zhaojin; Yang, Jinxing; Guang, Tianjia; Fan, Bingbing; Zhu, Kongjun; Wang, Xiaohui
Abstract: The sluggish Li‐ion diffusivity in LiFePO4, a famous cathode material, relies heavily on the employment of a broad spectrum of modifications to accelerate the slow kinetics, including size and orientation control, coating with electron‐conducting layer, aliovalent ion doping, and defect control. These strategies are generally implemented by employing the hydrothermal/solvothermal synthesis, as reflected by the hundreds of publications on hydrothermal/solvothermal synthesis in recent years. However, LiFePO4 is far from the level of controllable preparation, due to the lack of the understanding of the relations between the synthesis condition and the nucleation‐and‐growth of LiFePO4 . In this paper, the recent progress in controlled hydrothermal/solvothermal synthesis of LiFePO4 is first summarized, before an insight into the relations between the synthesis condition and the nucleation‐and‐growth of LiFePO4 is obtained. Thereafter, a review over surface decoration, lattice substitution, and defect control is provided. Moreover, new research directions and future trends are also discussed. Abstract : Aiming at the synthesis of high‐performance LiFePO4, the research progress in controlled hydrothermal/solvothermal synthesis of LiFePO4 in recent years is comprehensively reviewed and the relationship between reaction condition and nucleation and growth of LiFePO4 is summarized. Moreover, surface decoration, lattice substitution, and defect control of hydrothermally/solvothermally synthesized LiFePO4 are discussed.